(untitled) - DESY WULANDARI, RISMA (LATERNE, 2014)
ABSTRAK In der Untersuchung wird die Anwendung der Sprachspiele „die Flüsterkette (whisper race)“ im deutschen Hörverstehen versucht. Der Sprachspiele „die Flüsterkette (whisper race)“ wird anwendet, damit die Schülern aktiver sein, deutschen Hörverstehen zu folgen. Das Formulierungsproblem dieser Untersuchung sind : (1) Wie sind die Aktivitäten der Schülern im deutschen Hörverstehen mit der Sprachspiele „die Flüsterkette (whisper race)“? (2) Wie sind die Lernergebnisse der Sprachspiele „die Flüsterkette (whisper race)“ bei der Hörfertigkeit in der Klasse XI IPA 7 an der SMA Negeri 1 Krian?. Die Ziele dieser Untersuchung sind : die Aktivität der Schülern im deutschen Hörverstehen mit der Sprachspiele „die Flüsterkette (whisper race)“ zu beschreiben und die Lernergebnisse der Sprachspiele „die Flüsterkette (whisper race)“ bei der Hörfertigkeit in der Klasse XI IPA 7 an der SMA Negeri 1 Krian zu wissen. Diese Untersuchungsmethode ist eine qualitative und die Datenanalyse von dieser Untersuchung ist diskriptiv. Die Ergebnisse der Untersuchung werden gezeigt : (1) Die Aktivität der Schülern im deutschen Hörverstehen steigern. In der ersten Sitzung ist 53,75% und es gehört zur Kategorie „mittel“. In der zweiten Sitzung ist 67% und es gehört zur Kategorie „hoch“, in der dritte Sitzung ist 82,5% und es gehört zur Kategorie „sehr hoch“. (2) Der Durchschnitt der Lernergebnisse bei der Hörfertigkeit steigern, von pre-test ist 51,9 wird 70,3 in post-test. Schluesselwort : der Sprachspiele „die Flüsterkette (whisper race)“, Hörfertigkeit ABSTRACT This research is examined the implementation of the language game “Whisper Race” in German language learning listening skill. The language game “Whisper Race” is applied, so that the students more active in participating in the learning process of listening skill. This research problem are : (1) how are the Student’s activities in the learning process of listening skill?. (2) how are the results of the study of eleventh grade students of science class 7 of SMAN 1 Krian through the implementation of the language game “Whisper Race”?. The purpose of this research is to describe the student’s activities in the learning process of listening skill and to know the result of the study of the German listening skill with the language game “Whisper Race”. This research uses a qualitative method that will be described in a descriptive. The research is lasted for three meetings. The first meeting of the learning process carried out without the language game “Whisper Race”. Then the second and the third meeting of the learning process carried out with the language game “Whisper Race”. This research results are: (1) The student’s activities during the learning process of listening skill have increased. This can be seen from the percentage of the overall aspects of the assessment of student’s activity, the first meeting is 53,75% with categories “moderate”, the second meeting is 67% with categories “high” and the third meeting ist 82,5% with categories “very high”. (2) The listening skill of eleventh grade students of science class 7 of SMAN 1 Krian have increased. From the result of pre-test and post-test the average of students learning in listening skill have increased, from 51,9 in pre-test to 70,3 in post-test. Keyword : the language game “Whisper Race”, listening